Perceptions of Social Mobility: Development of a New Psychosocial Indicator Associated with Adolescent Risk Behaviors - Ritterman Weintraub, Miranda Lucia; Fernald, Lia C. H.; Adler, Nancy; Bertozzi, Stefano; Syme, S. Leonard (Frontiers in Public Health, 2015)
Social class gradients have been explored in adults and children, but not extensively during adolescence. The first objective of this study was to examine the association between adolescent risk behaviors and a new indicator of adolescent relative social position, adolescent “perceived social mobility.” Second, it investigated potential underlying demographic, socioeconomic and psychosocial determinants of this indicator. Data were taken from the 2004 urban adolescent module of Oportunidades, a cross-sectional study of Mexican adolescents living in poverty. Perceived social mobility was calculated for each subject by taking the difference between their rankings on two 10-rung ladder scales that measured (1) projected future social status and (2) current subjective social status within Mexican society. Adolescents with higher perceived social mobility were significantly less likely to report alcohol consumption, drinking with repercussions, compensated sex, police detainment, physical fighting, consumption of junk food or soda, or watching ≥ 4 hours of television during the last viewing. They were significantly more likely to report exercising during the past week and using a condom during last sexual intercourse. These associations remained significant with the inclusion of covariates, including parental education and household expenditures. Multiple logistic regression analyses show higher perceived social mobility to be associated with staying in school longer and having higher perceived control. The present study provides evidence for the usefulness of perceived social mobility as an indicator for understanding the social gradient in health during adolescence. This research suggests the possibility of implementing policies and interventions that provide adolescents with real reasons to be hopeful about their trajectories.